EVALUASI PROGRAM PRAKTIK KERJA LAPANGAN DALAM PEMBERLAKUAN MAGANG PADA KURIKULUM JURUSAN PENDIDIKAN ILMU PENGETAHUAN SOSIAL BERBASIS KKNI - Bashith, Abdul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Department of Social Sciences Education Faculty of Tarbiyah and Teacher Training (FITK) conducts Field Work Practice (PKL) for students at leading schools / madrasahs in East Java. On an ongoing basis the activities are developed with an internship pattern following the provisions in the framework of Indonesian national qualification (KKNI). The purpose of this study focuses on the evaluation of the implementation of field work practices in applying internships to the curriculum of social science education based on KKNI. This research uses qualitative approach, especially using evaluation research. From the results of the discussion can be concluded: (1) The results of monitoring and supervision of the implementation of field work practices conducted by using standardized statement instrument sheet, (2) Responses and evaluations regarding the implementation of field work practicesÂ showed good results in terms of administration, This internship program is an integral partÂ for students of IPS FITK UIN Maulana Malik Ibrahim Malang. Suggestions that can be recommended from the results of this study are: (1) Implementation of a good street vendors can be continuously improved and updated in technical implementation with electronic electronic systems based online, (2) Evaluation of the good about street vendors continue to be maintained and improved by establishing More intensive communication between the parties concerned, (3) Enrollment of apprenticeship in the curriculum of social science education based on KKNI that has been designed and set out to be a special marker character must be maintained and guarded in its implementation and constantly evaluated periodically and continuously in the improvementKeywords: Evaluation of PKL, Enforcement of Internship, Curriculum of Education of Social Sciences Based KKNI.